A History of Islamic Philosophy. - Majid Fakhry (New York, Columbia University Press, 1983)
The author discusses "the legalism, rationalism, and mysticism of Islamic thought and its impact on the cultural aspects of Muslim life."--Cover.
Include Bibliography Reference and Index Material.
Keywords: History; Islamic philosophy History; Islamic philosophy